CSABA VARGA – In Memoriam - KRISTÁLY, Alexandru (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
This note is devoted to present the scientific work of Professor Csaba Varga (1959-2021), who had contributions in Calculus of Variations and its applications in the theory of Partial Differential Equations and Finsler Geometry. Mathematics Subject Classification (2010): 35A15, 35B38, 58J05, 58J60.